2012
DOI: 10.1136/thoraxjnl-2011-200832
|View full text |Cite
|
Sign up to set email alerts
|

Early antibiotic treatment forPseudomonas aeruginosaeradication in patients with cystic fibrosis: a randomised multicentre study comparing two different protocols

Abstract: Background Pseudomonas aeruginosa chronic pulmonary infection is an unfavourable event in cystic fibrosis. Bacterial clearance is possible with an early antibiotic treatment upon pathogen isolation. Currently, no best practice exists for early treatment. The efficacy of two different regimens against initial P aeruginosa infection was assessed. Methods In a randomised, open-label, parallel-group study involving 13 centres, the superiority of inhaled tobramycin/oral ciprofloxacin compared with inhaled colistin/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
4
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 36 publications
7
104
4
10
Order By: Relevance
“…Subsequent studies, such as the ELITE and EPIC studies, have shown that inhaled tobramycin for 4 wk is also an effective antibiotic eradication therapy (Ratjen et al 2010;Treggiari et al 2011). In two small studies, no difference was identified between these two regimes with a comparable eradication rate (Taccetti et al 2012;Proesmans 2013).…”
Section: Antibiotic Therapy For Infection With P Aeruginosa Eradicatmentioning
confidence: 99%
“…Subsequent studies, such as the ELITE and EPIC studies, have shown that inhaled tobramycin for 4 wk is also an effective antibiotic eradication therapy (Ratjen et al 2010;Treggiari et al 2011). In two small studies, no difference was identified between these two regimes with a comparable eradication rate (Taccetti et al 2012;Proesmans 2013).…”
Section: Antibiotic Therapy For Infection With P Aeruginosa Eradicatmentioning
confidence: 99%
“…Odločno zdravljenje prve okužbe s PA je premaknilo začetek kronične okužbe s to bakterijo za 3,5 let pri skoraj 80 % otrok. 15,16 PregledNi člaNek/reView Osebe, ki pa že imajo kronično okužbo s PA, je potrebno doživljenjsko zdraviti z inhalacijskimi antibiotiki npr. tobramicinom.…”
Section: Zdravljenje Akutnih Okužb In Dolgotrajno Zdravljenjeunclassified
“…Эрадикация в конце курса лечения была схожей: 90% в группе ципрофлоксацин + колистин и 79% -в группе тобрамицина. Исследование показало, что 3 мес лечения ингаляционным колистином вместе с пероральной формой ципрофлоксацина и 28-дневный курс монотерапии тобрамицином имеют высокую и схожую эффективность с 80-90% эрадикацией P. aeruginosa по окончании курса лечения Раствор тобрамицина для ингаляций совместно с пероральной формой ципрофлоксацина против раствора колистина для ингаляций и пероральной формой ципрофлоксацина для терапии ранней инфекции P. aeruginosa [29] Исследование …”
Section: название исследования резюмеunclassified